Hydrogen Sulfide Inhibits Ferroptosis in Cardiomyocytes to Protect Cardiac Function in Aging Rats - Liang, Zihui; Miao, Yuxin; Teng, Xu; Xiao, Lin; Guo, Qi; Xue, Hongmei; Tian, Danyang; Jin, Sheng; Wu, Yuming (Frontiers in Molecular Biosciences, 2022)
Aging is the main factor of cardiovascular disease and cardiac function decline, in order to explore the reasons for the decline of cardiac function in the elderly, two hundred and thirty-one relevant clinical sample data and blood sample were collected. We found that, with the progress of aging, cardiac function decline, left ventricle remodeling, and cardiac function is negatively correlated with age; The level of serum hydrogen sulfide(H2S)decreased, while the level of serum malondialdehyde (MDA)and iron increased in healthy with aging. After that, animal model of aging rats and iron-overload rats was constructed for in vivo research. In animal experiments, we found the expression of endogenous H2S producing enzymes decreased, and the level of endogenous H2S decreased, the level of oxidative stress rised, the regulation ability on iron metabolism and the maintenance ability of iron homeostasis declined, the accumulation of MDA and iron led to the ferroptotic cell death, eventually caused myocardial injury and deteriorate cardiac function in rats, and high iron diet(HID) can accelerate the aging process and death of rats. The decline of cardiac function in aging rats and iron-overload rats may be caused by ferroptosis of cardiomyocytes. Exogenous H2S could enhanced the expression of endogenous H2S producing enzymes and promote endogenous H2S production, could regulating iron metabolism and reduce the level of oxidative stress, the protective effect of H2S on cardiac function in aging rats and iron-overload rats may be partly achieved by inhibiting ferroptosis of cardiomyocytes. Our present research demonstrated that the decline of cardiac function associated with aging is closely related to the decrease of endogenous H2S level and myocardial ferroptosis. H2S could regulating iron metabolism and reduce the level of oxidative stress of cardiomyocytes, inhibited ferroptosis of cardiomyocytes and protected cardiac function in aging rats.